1996
DOI: 10.1046/j.1365-2249.1996.d01-620.x
|View full text |Cite
|
Sign up to set email alerts
|

Subclasses of IgA antibodies in serum and saliva samples of newborns and infants immunized against rotavirus

Abstract: Little is known about subclass levels of IgA in serum or saliva of infants in the perinatal period. We have previously shown that very young infants are capable of responding to an experimental rotavirus vaccine with both serum and salivary IgA, and that small amounts of IgA are already detectable in cord blood of these infants. In the present study, total IgA1 and IgA2 antibodies in serum and saliva samples of some of these infants at birth, at 6 weeks of age, and at 12 weeks of age, were determined by a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The rotavirus-specific subclass response documented in this study is similar to that shown for children in developed countries where little or no IgA2 responses were seen [Friedman et al, 1996] and IgG1 and IgG3 subclass responses predominated [Grauballe et al, 1986]. The reason for the predominance of IgA1 to IgA2 can be severalfold, but one factor influencing the IgA subclass response is the character of the antigen; thus, bacterial polysaccharides induce an IgA2 response, and protein antigens induce an IgA1 response [Mestecky et al, 1999].…”
Section: Discussionsupporting
confidence: 82%
“…The rotavirus-specific subclass response documented in this study is similar to that shown for children in developed countries where little or no IgA2 responses were seen [Friedman et al, 1996] and IgG1 and IgG3 subclass responses predominated [Grauballe et al, 1986]. The reason for the predominance of IgA1 to IgA2 can be severalfold, but one factor influencing the IgA subclass response is the character of the antigen; thus, bacterial polysaccharides induce an IgA2 response, and protein antigens induce an IgA1 response [Mestecky et al, 1999].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, jacalin binds specifically to the human IgA1 subclass [Roque-Barreira et al, 1985;Kondoh et al, 1986]. Several studies have found that the IgA1 subclass is predominant in both infant sera and in saliva [Fitzsimmons et al, 1994;Friedman et al, 1996]. The IgA-RIP assay performed in this study included jacalin-agarose beads and high salt concentrations in the buffer instead of SDS in order to foster the detection of antibodies to conformation-dependent epitopes, as previously described [Johansen et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…The high values of salivary sIgA have to be taken into account when evaluating the potential of the immune system of newborn infants not only against microbial invasion in general but also with respect to the role of sIgA in the immune response to vaccination, e.g. against rotavirus [25], as well as in effector functions during allergic inflammation [26].…”
Section: Discussionmentioning
confidence: 99%